Light, electron microscopy and DNA sequences of the dinoflagellate Prorocentrum concavum (syn. P. arabianum) with special emphasis on the periflagellar area - Mohammad Noor, Normawaty; Moestrup, Ojvind; Daugbjerg, Niels (The International Phycological Society, 2007)
We have reexamined the original culture of Prorocentrum arabianum Morton et Faust (CCMP 1724) using a combination of light and electron microscopy in addition to gene sequence data. Compared to the original description of P. arabianum (Morton et al. 2002), the new observations revealed it to possess two pyrenoids surrounded by starch sheaths and two types of valve pores, but marginal pores were absent. Cells kept in culture for nearly a decade now appeared symmetrical to asymmetrical in outline rather than asymmetrical as in the original description. In culture, P. arabianum attached to the bottom of culture flasks instead of being an active swimmer. Also in culture it produced large amounts of mucus. Studying serial sectioned cells in the transmission electron microscope, the periflagellar area was seen to comprise nine platelets. The overall arrangement of platelets agreed with Taylor's scheme from 1980 except for one additional plate labeled a2 situated between a1, b and e. Further ultrastructural examination of P. arabianum revealed for the first time a connection between a pusule-like organelle surrounded by two membranes and the accessory pore within the periflagellar area. We speculate that the pusule canal is used for discharging mucus or particulate matter through the accessory pore. The LSU rDNA sequence divergence between P. arabianum and P. concavum isolated from Malaysia was only 0.2%. As such a low divergence value is usually seen only at the population level, we also determined nuclear-encoded ITS 1 and ITS 2 and the cytochrome b (cob) gene residing in the mitochondrial genome in the two taxa. These DNA fragments were identical (ITS 1 and ITS 2) or almost identical (cytochrome b) when comparing P. arabianum and P. concavum. Amalgamating all available information from ultrastructure and molecular data, we conclude that P. arabianum is a synonym of P. concavum. It should, however, be noted that there is a difference in toxin profile between the two isolates. A phylogeny based on partial LSU rDNA including 14 species of Prorocentrum and 40 other dinoflagellates indicated that the genus may comprise six groups, and each of these are supported by a combination of morphological features and toxin production. As statistical support from bootstrap values or posterior probabilities for the divergent branches in the LSU tree was low, we refrain from major systematic changes of the genus Prorocentrum until more species are examined in the electron microscope and new DNA fragments other than ribosomal genes become available.